International Symposium on Oilfield Chemistry 2003
DOI: 10.2118/80254-ms
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Dissolved Iron on the Performance of Scale Inhibitors Under Carbonate Scaling Conditions

Abstract: The laboratory determination of scale inhibitor (SI) performance under field specific conditions using dynamic or static scale inhibitor tests provides an important method for determining minimum inhibitor concentrations (MIC's) for the inhibition of scale growth. This paper will discuss the ability of small amounts of ferrous iron to dramatically reduce the ability of SI's to inhibit calcium carbonate scale formation under dynamic laboratory test conditions. It has been previously reported that the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…This has been shown both in sophisticated experiments examining additive-mediated growth in high energy synchrotron experiments 20,21 via atomic force microscopy 22 as well as in more conventional static and dynamic experiments similar to those shown here. Similarly Figure 2, taken from SPE 80254, 10 shows the dramatic impact of small concentrations of ferrous iron (FeII) on the morphology and composition of carbonate scales grown in microbore coils under dynamic conditions. Similarly Figure 2, taken from SPE 80254, 10 shows the dramatic impact of small concentrations of ferrous iron (FeII) on the morphology and composition of carbonate scales grown in microbore coils under dynamic conditions.…”
Section: Inhibitor Performance and Conventional Test Methodologiesmentioning
confidence: 98%
See 1 more Smart Citation
“…This has been shown both in sophisticated experiments examining additive-mediated growth in high energy synchrotron experiments 20,21 via atomic force microscopy 22 as well as in more conventional static and dynamic experiments similar to those shown here. Similarly Figure 2, taken from SPE 80254, 10 shows the dramatic impact of small concentrations of ferrous iron (FeII) on the morphology and composition of carbonate scales grown in microbore coils under dynamic conditions. Similarly Figure 2, taken from SPE 80254, 10 shows the dramatic impact of small concentrations of ferrous iron (FeII) on the morphology and composition of carbonate scales grown in microbore coils under dynamic conditions.…”
Section: Inhibitor Performance and Conventional Test Methodologiesmentioning
confidence: 98%
“…This allows for routine testing under; higher temperature conditions (> 100°C), 2,3, 6,9 in the presence of bicarbonate ions without loss of pH control, 2,3,5,8 Examination of systems in presence of dissolved iron is more readily achievable, provided feed brines are adjusted accordingly to prevent oxidation of Fe(II) -> Fe(III) 10 The main disadvantage of dynamic performance tests relates to extremely short residence time, generally of order < 10 seconds. This allows for routine testing under; higher temperature conditions (> 100°C), 2,3, 6,9 in the presence of bicarbonate ions without loss of pH control, 2,3,5,8 Examination of systems in presence of dissolved iron is more readily achievable, provided feed brines are adjusted accordingly to prevent oxidation of Fe(II) -> Fe(III) 10 The main disadvantage of dynamic performance tests relates to extremely short residence time, generally of order < 10 seconds.…”
Section: Inhibitor Performance and Conventional Test Methodologiesmentioning
confidence: 99%
“…A review of the historical water analysis prior to a failure for each well showed that dissolved ferrous iron is present in the water at about 200 to 300 ppm. It has been reported previously that soluble iron has an adverse effect upon the performance of conventional phosphonate-based and polyacrylic acid polymer scale inhibitors against carbonate scale (Graham et al, 2003, Smith et al 2008, Shen et al, 2011. Due to this relatively high iron concentration, it was surmised that the high rate of failures in the presence of normally sufficient scale inhibitor residuals were due to the effect of iron on the performance of scale inhibitor (Szymczak, et al, 2012).…”
Section: Bakken Scale Problem Statement and Solid Scale Inhibitor Designmentioning
confidence: 99%
“…• Successful remedial treatment to remove existing scale deposits prior to SISQ application • Preventing drop-out of waxes or other organic deposits in the near-wellbore and production system during the treatment, predominantly by keeping the temperature of injected fluids above WAT • Selection of a non-damaging scale inhibitor product suitable for application in this sensitive reservoir • Evaluation of the likely impact of low levels of produced iron on scale inhibitor performance 3,4 • Developing suitable treatment designs to achieve adequate placement along the full length of Mangala's horizontal wells. [5][6][7][8] The remainder of this paper discusses how these requirements were satisfied for the initial squeeze treatments in the Mangala field.…”
Section: Chemical Selection-overviewmentioning
confidence: 99%